2010
DOI: 10.1111/j.1365-2354.2009.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health and safety of personnel handling chemotherapeutic agents in Greek hospitals

Abstract: The expansion of chemotherapy raised concerns about the health and safety of hospital personnel. Very little is known about the conditions of handling of chemotherapeutic agents by healthcare workers in Greece and possible adverse effects related to their safety practices, as well as the safety policies adopted by the Greek hospitals. A self-evaluation questionnaire was completed by 353 healthcare workers involved with the use of chemotherapeutic drugs in 24 Greek hospitals and the answers were statistically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
3
26
1
1
Order By: Relevance
“…Most of the nurses were aware of the needs for continuous education and positive effects of education. These results are in accordance with Constantinidis's findings that reported a poor potential for ongoing education (22). Therefore, there is a desperately need for designing an ongoing training program by expert pharmacists in order to enhance and update nurses' knowledge in handling of ANPDs.…”
Section: Knowledgesupporting
confidence: 81%
See 3 more Smart Citations
“…Most of the nurses were aware of the needs for continuous education and positive effects of education. These results are in accordance with Constantinidis's findings that reported a poor potential for ongoing education (22). Therefore, there is a desperately need for designing an ongoing training program by expert pharmacists in order to enhance and update nurses' knowledge in handling of ANPDs.…”
Section: Knowledgesupporting
confidence: 81%
“…Training in various subjects showed different effects on nurses' knowledge scores. Constantindis et al reported that a significant percentage of respondents had no relevant information and only 29.6% of health care workers had received training for preparation and reconstruction of chemotherapeutical agents (22).…”
Section: Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the majority of the health workers did not have access to it. This revelation is in contrary to the suggestions by Work Safe Victoria [25] which indicates that policy procedures should be available, communicated to and understood by all employees as an important part of implementation of Occupational Health Services. However, training and education on risk mitigation in OHS, a safe working environment and equity in the workplace were provided in some of the departments.…”
Section: Legal and Regulatory Frameworkcontrasting
confidence: 49%